AN ANALYSIS OF METAPHOR TRANSLATION IN THE SUBTITLE OF SHERLOCK HOLMES 2: A GAME OF SHADOWS (2011) MOVIE - Siegfrieda Alberti Shinta Mursita Putri; Martha Sie (Lire Journal (Journal of Linguistics and Literature), 2019)
A metaphor has been a conflict in subtitling for its cultural-specific sense and challenging translatability. Consequently, the translators tend to omit the metaphors. This study attempts to find out the categories of conceptual metaphors and applied strategies in the subtitles of Sherlock Holmes 2: A Game of Shadows (2011). This study applies the Combined Strategies proposed by Lindqvist (Pedersen, 2015). The results indicate that analogy, personification, and image metaphors appear in the movie. The translator applies five of nine proposed strategies in this study. The most frequently applied strategies are word-for-word translation and paraphrase strategies. No omission occurs, but the study discovers that the translation appears to be less natural and fails to transfer the cultural essence from the English metaphors.